Implementasi Aplikasi Quizizz sebagai Media Pembelajaran dalam Menyikapi Era Revolusi Industri 4.0 di IAIN Padangsidimpuan - Hayati, Nursri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This paper is entitled Implementation of the Quizizz Application as a Learning media for Fifth Semester Students of the Aqidah Akhlak Learning Course at the PAI Faculty of Tarbiyah and teacher Training at IAIN Padangsidimpuan. This study aims to find out how the steps for implementing the Quizizz Apllication as learning media for students in the fifth semester of the Aqidah Akhlak Learning Course at the PAI Program Faculty of Tarbiyah and Teacher Training IAIN Padangsidimpuan, What are the obstavle faced in implementing the quizizz applicatin as a learning media in the acurse aqidah and akhlak in the fifth semester of PAI IAIN Padangsidimpuan. This study uses a qualitative approach with descriptve analysis methode. Data collection by using intruments of interviews, documentation, and observation. Then analyzed using triangulation techniques. The results of this study indicate that the use of the quizizz application as a learning media is an alternative solution in online learning and is an effort to respond the digital-based industrial revolution 4.0 era. The quizizz application is in the form of an online game that contains learning material for moral aqidah, which attraccts student`s interest and enthusiasm because the presentation of this application is interactive and communicative. Constraints faced in the use of this quizizz application are related to network problems. Unstable network conditions in the student residence area. Another obstacle in implementing this application is that are students who use two accounts when joining quizizz.